Development across faith boundaries - Clarke, Matthew, 1969-; Ware, Anthony, 1966- (London ; New York : Routledge, 2017)
"Faith-based organisations (FBOs) have long been recognised for their success in delivering programs and interventions amongst communities of the same faith. However, many FBOs today work across a variety of contexts with both secular NGOs and donors as well as local partners and communities from different faiths. Development Across Faith Boundaries explores the dynamics of activities by local or international FBOs which cross faith boundaries, whether with their partners, donors or recipient communities. The book investigates the dynamics of cross-faith partnerships in a range of development contexts, from India, Cambodia and Myanmar, to Melanesia, Bosnia, Ethiopia and Afghanistan. The book demonstrates how far FBOs extend their activities beyond their own faith communities and considers the impacts of these cross-faith partnerships, such as their work on conflict and sectarian or ethnic tension in the relevant communities. This book is an invaluable guide for graduates, researchers and students with an interest in development and religious studies, as well as practitioners within the aid sector"--
pt. 1. Introduction -- pt. 2. Case studies -- pt. 3. Conclusions.
Keywords: Economic development -- Religious aspects; Religion and social problems